Impact of anti-doping education and doping control experience on anti-doping knowledge in Japanese university athletes: a cross-sectional study - Yuka Murofushi; Yujiro Kawata; Akari Kamimura; Masataka Hirosawa; Nobuto Shibata (BMC, 2018)
Abstract Background This study was conducted to elucidate the anti-doping (AD) education, doping control experience, and AD knowledge according to the World Anti-doping Code (Code) of Japanese university athletes. Methods We collected data from 514 male athletes (Mage = 19.53 years, SD = 1.13) and 629 female athletes (Mage = 20.99 years, SD = 1.07). We asked them about their experience undergoing doping control and the AD education they had received. Then, we assessed their AD knowledge using the World Anti-Doping Agency's Athlete Learning Program about Health and AD (ALPHA) test. Results The results showed that 2.54% of the participants had undergone doping control. Further, 30.10% received AD education at least once, and 20.82% received AD education more than once. When comparing the ALPHA scores of athletes with/without doping test experience, we observed no significant difference. However, the ALPHA scores of athletes with/without AD education were significantly different; specifically, athletes who received AD education more than once had significantly higher ALPHA scores than non-educated athletes. Conclusion These results revealed that doping control experience was not related to AD knowledge and that AD education was associated with AD knowledge, suggesting that athletes who receive AD education more than once have more accurate AD knowledge than less educated athletes on this topic. The importance of AD education in promoting understanding of AD according to the Code in sports is highlighted in this study.